Biopsychosocial Analysis of Factors on COVID-19 Screening Awareness of Infertile Couples in Assisted Reproductive Technology - Budihastuti, Uki Retno; Laqif, Abdurahman; Melinawati, Eriana; Prakosa, Teguh; Udiyanto, Hermawan; Priyanto, Heru Priyanto; Darto, Darto; Rantasari, Affi Angelia; Wasyanto, Trisulo; Anggraeni, Asih; Wijayanti, Agung Sari (Journal of Maternal and Child Health, 2021)
Background: The development of screening methods for infertility patients during the Coronavirus-2019 (COVID-19) pandemic provides new challenges in the adaptation of children's want programs in the era of the COVID-19pandemic. Several screening methods have been developed but various factors affect the awareness of couples to want to do COVID-19 screening. This study aimed to analyze biopsychosocial factors associated with awareness of COVID-19 screening in infertile couples. Subjects and Method: A cross-sectional study conducted at The Sekar Polyclinic of Dr. Moewardi Regional General Hospital during the COVID-19 pandemic. A number of 60 infertile couple of reproductive age who underwent the ART program was selected by random sampling. The dependent variable was awareness for COVID-19 screening. The independent variables were anxiety, knowledge, age, and length of infertility. The data were obtained from medical record and questionnaire and analyzed by a multiple logistic regression. Results: Anxiety (OR= 26; 95% CI; p<0.001) and above-average knowledge levels (OR=16; 95% CI; p<0.001) affected awareness for COVID-19 screening. While the age and length of infertility do not affect awareness for COVID-19 screening (p >0.05). Conclusion: Anxiety and above-average knowledge levels affect awareness for COVID-19 screening.